The Effect of Guided Writing Strategy in Writing Skill - Ni Made Lisma Martarini; Ni Nyoman Ayu J. Sastaparamita (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The present study is dealt with the effect of guided writing strategy through first semester students in STMIK STIKOM INDONESIA. The method of analyzing data in this research was conducted by the descriptive analysis. Before that, simple random sampling was used to determine the sample. Two groups were treated differently. One group treated by a guided writing strategy and the other treated by a conventional writing strategy. The data in this study analyzed solely in a descriptive way. The descriptive analysis of the study includes measures of central tendency or averages (mean, median, and mode) and measures of spread or dispersion (standard deviation, variance, and range). The result showed that when the students were treated by guided writing the mean of the result was 80.08 meanwhile when the students were0 treated by conventional writing skill was 76.77. Strengthened by the descriptive analysis, it was found that the mean score of writing competency tests for the students who treated by using guided writing strategy was 80.76 and the mean score of writing competency treated by using conventional writing strategy was 76.76. From the mean score finding, it can be concluded that according to learning strategy, the group of students treated by using guided writing strategy was better than the students treated by using conventional writing strategy.